LEGAL ASPECT OF THE SALE OF LAND CONSTITUTING REGIONAL ASSETS - Irpan Suriadiata (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
The regulation that sets the position of the state in land management is very plural. The Such as regulation in the Netherland colonialism Colonialism era which put positioned the state as owner of the land under the principle of domein verklaring. In During the old regime, the principle of domein verklaring is no longer exist by the established of UUPA (Law of the land) where the principle of domein verklaring was abolished and stated as no longer valid. In the new regime, the UUPA was uphold but no longer became the basic regulation of land matters. and in In the reformation era although the UUPA is still existed but beside that, also there are specific Law that positioned the state/ regions as the land owner according to in accordance with the principle of domein verklaring principle. Basically the state/regions are not the owner of the land so they have no right to sale sell the land. Nevertheless, Even thought after the reformation era there are several law and regulation which allowing the region local government to sale sell the local government asset of land assets of the region. Thus, These such regulation has become the legal basic basis for the region local government to sale sell their land assets the asset of land as what has been done did by the government of west West Lombok region because the law basically did not allow the sate to sell the asset of land, the sale of land by the West Lombok Government is illegal.Keywords: Legal Aspects, The Sale of Land Assets of The Region